Safety and efficacy of oral fexinidazole in children with gambiense human African trypanosomiasis: a multicentre, single-arm, open-label, phase 2–3 trial. Issue 11 (November 2022) - Kande Betu Kumesu, Victor; Mutombo Kalonji, Wilfried; Bardonneau, Clélia; Valverde Mordt, Olaf; Ngolo Tete, Digas; Blesson, Séverine; Simon, François; Delhomme, Sophie; Bernhard, Sonja; Nganzobo Ngima, Pathou; Mahenzi Mbembo, Hélène; Fina Lubaki, Jean-Pierre; et al.
Summary: Background: Fexinidazole has been reported as an effective oral monotherapy against non-severe gambiense human African trypanosomiasis in a recent trial in adults. We aimed to assess the safety and efficacy of fexinidazole in children across all disease stages of gambiense human African trypanosomiasis. Methods: We did a multicentre, single-arm, open-label, phase 2–3 trial at eight district hospitals in the Democratic Republic of the Congo. We recruited children with a Karnofsky score of more than 50, those aged 6 years to younger than 15 years, weighing 20 kg or more, and with confirmed gambiense human African trypanosomiasis (any stage). Children weighing 20 kg or more and less than 35 kg received oral fexinidazole of 1200 mg (two × 600 mg tablets) once per day for 4 days (days 1–4) followed by 600 mg (one × 600 mg tablet) once per day for 6 days (days 5–10). Children weighing 35 kg or more received oral fexinidazole of 1800 mg (three × 600 mg tablets) once per day for 4 days (days 1–4), followed by 1200 mg (two × 600 mg tablets) once per day for 6 days (days 5–10). The primary endpoint was fexinidazole treatment success rate 12 months after end of treatment. A rate greater than 80% was deemed acceptable and a target value of 92% was aimed for. Safety was assessed through routine monitoring. This study is completed and registered with ClinicalTrials.gov, number NCT02184689 . Findings: Between May 3, 2014, and Nov 22, 2016, we screened a total of 130 paediatric patients, of whom 125 (96%) received at least one dose of fexinidazole. All 125 patients (69 [55%] patients with stage 1, 19 [15%] with early stage 2, and 37 [30%] with late stage 2 gambiense human African trypanosomiasis) completed the 10-day treatment. Treatment success rate at 12 months was 97·6% (95% CI 93·1–99·5; 122 of 125 patients). The primary endpoint was met and the targeted value of 92% was exceeded. Treatment success at 12 months was elevated across all disease stages: 98·6% (95% CI 92·2–99·9; 68 of 69 patients) in stage 1, 94·7% (74·0–99·9; 18 of 19 patients) in early stage 2, and 97·3% (85·8–99·9; 36 of 37 patients) in late stage 2 gambiense human African trypanosomiasis. No new safety issues were observed beyond those found in adult trials. Overall, 116 (93%) of 125 patients reported 586 treatment-emergent adverse events, mainly mild or moderate. The most frequently reported treatment-emergent adverse events of interest during hospital admission were vomiting (86 [69%] of 125) and headache (41 [33%]). Seven (6%) of 125 patients had severe malaria, which was often accompanied by anaemia that was unrelated to fexinidazole. One patient died following dyspnoea and injury due to traumatic aggression 172 days after end of treatment, which was considered unrelated to fexinidazole or gambiense human African trypanosomiasis. Interpretation: Oral fexinidazole is a safe and effective first-line treatment option across all gambiense human African trypanosomiasis disease stages in paediatric patients. Funding: Through the Drugs for Neglected Diseases initiative: the Bill & Melinda Gates Foundation (USA), the Republic and Canton of Geneva (Switzerland), the Dutch Ministry of Foreign Affairs (Netherlands), the Norwegian Agency for Development Cooperation (Norway), the Federal Ministry of Education and Research through KfW (Germany), the Brian Mercer Charitable Trust (UK), and other private foundations and individuals from the human African trypanosomiasis campaign. Translation: For the French translation of the abstract see Supplementary Materials section.